Analysis of the Implementation of Financial Reporting Based on PSAK 109 at the National Zakat Agency (BAZNAS) of Padang Pariaman Regency - M Erinaldo Tanjung; Ilham Illahi2 (Darul Yasin Al Sys, 2026)
The implementation of financial reporting standards is essential for ensuring transparency, accountability, and public trust in zakat management institutions; however, the extent to which the financial reporting practices of the National Zakat Agency (BAZNAS) of Padang Pariaman Regency comply with PSAK 109 requires systematic examination. This study aimed to analyze the implementation of PSAK 109 in the recognition, measurement, presentation, and reporting of zakat, infaq, and sadaqah funds. A descriptive qualitative approach was employed, with data collected through observations, interviews, and documentation of BAZNAS financial reports for the 2023–2024 period. The data were analyzed through data reduction, data presentation, and conclusion drawing. The findings indicate that the recognition and measurement of transactions and the preparation of financial statements at BAZNAS Padang Pariaman generally comply with PSAK 109. The statements of financial position, changes in funds, changes in managed assets, cash flows, and notes to the financial statements were prepared systematically and periodically, thereby supporting institutional transparency and accountability. Nevertheless, a compliance issue was identified in the use of non-sharia funds to cover a deficit in the amil fund, which is inconsistent with PSAK 109. The study concludes that BAZNAS Padang Pariaman has substantially implemented PSAK 109, although stricter adherence to provisions governing non-sharia funds remains necessary. These findings contribute to the evaluation of accounting practices in zakat institutions and emphasize the importance of strengthening financial governance to enhance accountability, transparency, and public trust in zakat management.